Organization and functioning of school inspection on the basis of the principle of specialization - Toledano Peláez, Juan José (Avances en Supervisión Educativa, 2024)
The aim is to provide some reflection on the principle of specialization in school inspection and its implementation in the current models of the different educational administrations. It is postulated, as a simple possibility, the usefulness of another organic and functional model that could be set up on the basis of a fostering of this principle, as a way of optimizing the contribution to the improvement of the quality of the educational system, and the consequences and implications that this would have on the way of activating the functions of School Inspection, planning its ways of working and executing its tasks and actions, something by no means easy or evident.With respect to the contribution to this improvement, there is a widespread opinion that School Inspection has not yet managed to reach a satisfactory model of intervention on the educational system and school centres for the fulfilment of this purpose, taking advantage of all the potential that inspectorate could provide from other organizational and operational approaches different from the current ones. This could be carried out through in-depth evaluative actions by specialized teams. Specialization can thus be conceived as a key factor for this purpose, which could therefore be enhanced.